The Impact of WeChat Platform on Social Interaction Under the Perspective of Situational Theory - Shu, Qian (Transactions on Social Science, Education and Humanities Research, 2024)
The new media environment will promote new interactions and relationships. This paper attempts to use the situation theory of media to explore the impact of the WeChat platform on social behavior and analyze the new communication scenes created by the WeChat platform, and the new communication scenes have changed the interaction behavior and communication relationship. These issues have become an important exploration of the current in-depth understanding of online social media. This essay combines and summarizes the new media situations that WeChat has constructed and discuss the influences of these situations on social interactions according to situation theory. This research also explores how WeChat scenario affects its clients’ communication behaviors and relations through the methodology of depth interview, questionnaires and participatory-observation. Through the combing of the media scenes and their influences on WeChat and expand the analysis of the two virtual scenes of group chat and circle of friends. The user realizes the common presence of the virtual body through the WeChat group chat scene.. In the circle of friends, the users have the autonomy to control the screen, and can switch the front and back areas in the scene of the circle of friends at will. WeChat makes the online and offline scenes continue to merge through the expansion of the offline acquaintance circle and the social interaction of strangers on the line at the same time. Using in-depth interviews and questionnaire surveys, the author finds that the interaction scene of WeChat construction has two effects on social interaction behavior. On one hand, some new methods of communications have emerged.  The virtual scenario socialization creates the interaction between human and machine, and the open scene of WeChat makes the user's personality and ability become their shining point which can makes them attractive. The user uses "likes" as a way of communication in the situations. On the other hand, the expression package came into being in order to provide more scene information. Situations changes in the front, middle, and back areas affect the user's expression package usage behavior.